PENGARUH PEMBERIAN MOTIVASI DAN KESELAMATAN DAN KESEHATAN KERJA(K3) TERHADAP SEMANGAT KERJA PADA KARYAWAN PT. ISS INDONESIA AREA IVO MAS TUNGGAL DUMAI - Wahyu Candika Aksana Putra; Okta Karneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the effect of providing motivation and occupational safety and health on employee morale at PT.ISS Indonesia Area Ivo Mas Tunggal Dumai. The independent variables are motivation (X1) and occupational safety and health (X2). While the dependent variable is work spirit (Y). In this research, the method used is descriptive quantitative analysis with SPSS 24.0 program. The population in this study were permanent employees totaling 60 people, with the sample technique used, namely census/total sampling. Data collection techniques through questionnaires and interviews, types and sources of data using primary data and secondary data, measurement collection techniques using a Likert scale. From data analysis which includes validity test, reliability test, simple linear regression analysis, multiple linear analysis, determination analysis and significance test with t test (partial) test, and f test (simultaneous). The results of this study indicate that the results of testing the first t test hypothesis, giving motivation to work morale, namely t count (3.205) > t table (2.00172), meaning that motivation has a positive effect on work morale. Both occupational safety and health on work morale are t count (3.049) > t table (2.00172), meaning that occupational safety and health has a positive effect on work morale. The results of the f test of providing motivation and occupational safety and health have a significant effect on work morale, namely f count (11,156) > (3.16) meaning that the provision of motivation and occupational safety and health simultaneously has a significant effect on work morale. Keywords: Motivation, Occupational Health and Safety, Work Spirit